Effects of Physical Activity and Mindfulness on Resilience and Depression During the First Wave of COVID-19 Pandemic - Antonini Philippe, Roberta; Schwab, Laurie; Biasutti, Michele (Frontiers in Psychology, 2021)
The first wave of the COVID-19 pandemic generated a significant number of stressors that the Swiss population had to deal with. In order to cope with and adapt to such adversity, it is essential to have protective factors that allow for resilience. The objective of this study was to investigate the effects of mindfulness and physical activity on depression and resilience during the first wave of the COVID-19 pandemic. A quantitative method was adopted asking participants who were engaged in physical activity or mindfulness to fill a battery of measures of depression and resilience and some demographic questions. The results showed that mindfulness practice strengthened the initial level of resilience of practitioners, suggesting that mindfulness meditation is a tool for coping with adversity during a potentially traumatic event. Conversely, physical activity practitioners maintained a stable resilience score over time, suggesting that exposure to adversity did not disrupt their state of biopsychospiritual homeostasis. Moreover, being physically active decreased the depression score over time. Regarding demographic variables, gender differences were observed in the average scores in the resilience scale and in the Depression Inventory.